Formação docente para educação inclusiva: análise das grades curriculares dos cursos de licenciaturas das universidades estaduais do Paraná - Araujo, Carla Cristina Varela (2023)
The increment in access and retention of students who require inclusion actions in regular education has been increasing in recent years. This demand requires a careful look at the structure necessary for inclusion to occur in a fullest way. This perspective must extend to teacher training, which are the foundation for inclusion process. The present study aims to analyze the curricula of undergraduate courses at the State Universities of Paraná, focusing on the course program of their disciplines, seeking to identify and characterize the disciplines related to the Inclusive Education approach. This is a qualitative research with an exploratory nature, whose methodology is based on documental analysis, with data analysis developed using the strategies recommended in the content analysis technique. As a theoretical framework for the analysis, we adopted the teaching knowledge necessary for inclusive education, which covers different dimensions of teacher performance, in particular, the attitudinal dimension, the procedural dimension, the conceptual dimension, the contextual dimension and the personal, associated with teaching characteristics. For the analysis procedure, we were based on the ideas of the content analysis technique, with the identification of context units (UC) and registration units, which allowed us to list the main characteristics of the body of subjects in the syllabi. During the analysis, we organized the syllabuses into two groups: syllabi that refer to inclusion explicitly in the subject titles and syllabuses that refer to inclusion only in the body of the syllabus text. The explanation of the theme in the title of the subject suggests that the focus should be related to inclusion, while in the second group, the subject appears together with other discussions or as transversal themes that must be addressed over all curricular components. In detailing the analysis of the syllabi, we observed that characteristics listed in the UC are compatible with teaching knowledge for inclusive education taken as a theoretical reference, making it possible to recognize that the subjects listed in the subject course program refer to teaching knowledge. Although the emphasis on UC is not homogeneous among institutions, in the majority all UC are covered, so that the knowledge of teachers necessary for inclusive education is met. It is worth noting, however, that although the themes covered include aspects related to all dimensions of teaching knowledge, this does not occur simultaneously, that is, depending on the discipline, the topics indicated in the syllabi focus on one or two dimensions of knowledge.